Semiotika dalam Novel Dompet Ayah Sepatu Ibu Karya J.S. Khairen (Charles Sanders Peirce) - Noplara, Intan; Fauzan, Akhmad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This research aims to describe the semiotics of icons, indices and symbols in the novel Dad's Wallet, Mother's Shoes by J.S. Khairen. The author uses a qualitative descriptive research type, the research object is studied in the form of semiotic signs, namely icons, indices and symbols using a semiotic approach, this research data is in the form of text, sentences, paragraphs or quotations related to signs or semiotic icons, indices and symbols. in the novel Dad's Wallet, Mother's Shoes by J.S. Khairen, the data collection technique uses reading and note-taking techniques, for the data validity technique this research focuses on testing the credibility of the data by triangulation, while the data analysis technique used is data reduction by summarizing or summarizing the main important things to provide a clearer picture. and easy to understand, presenting data by presenting it in the form of explaining or describing and classifying data according to the main problem, namely differentiated in explaining the types of signs so that they are neatly arranged and easy to understand, drawing conclusions or verification is done by comparing the suitability of the statements of the research object with the meaning the results contained in the form of a summary description of the entire content of the research. Based on the results of data analysis, eighty-six data were found, including (1) fourteen data icons, (2) twenty-six data indexes, and (3) forty-six data symbols. The signs found are related to culture and daily human life, where human life is full of hidden meanings so that these signs function to reveal signs in everyday life as a means of communication in order to find out about something.Keywords: Semiotics, novel Dad's Wallet, Mother's Shoes, icons, indices, symbols